The Relationship Between Feeding Patterns and Stunting Incidents in Toddlers Aged 12-59 Months in the Working Area of the Jelbuk Jember Community Health Center - Tirtana, Mochammad Arif; Kustin; Nafista, Ulfia Fitriani (Journal of Nursing Periodic, 2024)
Background: The prevalence of stunting in Jember Regency according to SSGI in 2022 is still at 34.9%, which is the highest figure in East Java. From the results of a preliminary study conducted by researchers, it was found that 356 children (17.8%) were stunted in the weighing month of February 2023 and 381 children (18.46%) were stunting in the weighing month of August 2023. The diet of toddlers plays a very important role in the process. growth in toddlers, because food contains many nutrients. Objective: The aim of this research is to analyze the relationship between feeding patterns and the incidence of stunting in toddlers aged 12-59 months in the Jelbuk Community Health Center working area, Jember Regency. Method: The method in this research is quantitative correlational with an observational approach and a cross-sectional research design. The total sample was 95 respondents using cluster sampling techniques with the Slovin formula. The measurement instrument for this research uses the CFQ (Child Feeding Questionnaire) questionnaire, then assesses stunting in toddlers using microtoise measurements and converts it into a standardized value (Zscore) using the WHO-2005 anthropometric standards for toddlers. Results: The results of this study show that the majority of respondents have inappropriate eating patterns, 61 (64.2%) respondents, and the majority of respondents experience stunting, 65 (68.4%) respondents. The results of the Spearman's Rho statistical test show that the p-value value = 0.000 so there is a significant relationship between feeding patterns and the incidence of stunting in toddlers aged 12-59 months. Discussion: When mothers adopt an appropriate diet, the incidence of stunting in toddlers is lower, whereas when mothers adopt an inappropriate diet, the incidence of stunting in toddlers has the potential to increase.